An Exploratory Investigation of the Photophysical and Photochemical Properties of Rhenium(I) N-Heterocyclic Carbene Tricarbonyl Complexes - Vaughan, Jamila Glorian (Curtin University, 2017)
Functionalised N-heterocyclic carbene (NHC) ligands were synthesised, characterised and coordinated to a rhenium metal centre. The resulting rhenium(I) NHC tricarbonyl complexes were emissive when irradiated with UV light. These photophysical properties were analysed and quantified. During this analysis it was noted that some of the complexes exhibited photochemically activated ligand substitution reactions dependent of the functionality of the ligand. The unique mechanism of these reactions was investigated using synthetic and spectroscopic techniques.